Building and rebuilding N‐glycans in protein structure models. Issue 4 (16th April 2019) - van Beusekom, Bart; Wezel, Natasja; Hekkelman, Maarten L.; Perrakis, Anastassis; Emsley, Paul; Joosten, Robbie P.
Abstract : Carbohydrates are automatically built and rebuilt using Coot in the PDB‐REDO pipeline. Abstract : N‐Glycosylation is one of the most common post‐translational modifications and is implicated in, for example, protein folding and interaction with ligands and receptors. N‐Glycosylation trees are complex structures of linked carbohydrate residues attached to asparagine residues. While carbohydrates are typically modeled in protein structures, they are often incomplete or have the wrong chemistry. Here, new tools are presented to automatically rebuild existing glycosylation trees, to extend them where possible, and to add new glycosylation trees if they are missing from the model. The method has been incorporated in the PDB‐REDO pipeline and has been applied to build or rebuild 16 452 carbohydrate residues in 11 651 glycosylation trees in 4498 structure models, and is also available from the PDB‐REDO web server. With better modeling of N‐glycosylation, the biological function of this important modification can be better and more easily understood.